Small for gestational age infants and the association with placental and umbilical cord morphometry: a digital imaging study. (1st November 2020) - Ismail, Khadijah I.; Hannigan, Ailish; Kelehan, Peter; Fitzgerald, Brendan; O'Donoghue, Keelin; Cotter, Amanda
Abstract: Introduction: Individual placental and umbilical cord morphometry have been previously identified to have an association with fetal growth. This study aims to identify which of the morphometric measurements in combination are associated with pregnancies with small for gestational age (SGA) infants using digital imaging of the delivered placenta. Material and methods: This study examined 1005 placentas from consecutively delivered singleton pregnancies in a tertiary center. Standardized images of each placenta were taken. Placental weight and thickness; umbilical cord length and diameter were measured on gross examination. Distance from the placental cord insertion site to placental margin, length and breadth of the placenta and placental chorionic surface area were measured digitally using ImageJ software. Logistic regression models and area under the curve (AUC) were used to identify the best subset of morphometric measurements to classify infants as SGA (<10th centile). Results: Overall, 141 (14%) infants were SGA. The morphometric measurements at delivery most strongly associated with the classification of infants as SGA were placental weight (AUC = 0.806) and placental surface area (AUC = 0.749). Of the potential antenatal morphometric measurements, umbilical cord diameters, both placental (AUC = 0.644) and fetal end (AUC = 0.629) were most strongly associated with SGA. A logistic regression model with maternal age, smoking status, current history of preeclampsia, umbilical cord length, placental weight, birthweight-to-placental weight ratio and umbilical cord diameter (placental end) had a sensitivity of 53% and a false-positive rate of 2% (AUC = 0.945) for the classification of infants as SGA. Conclusion: Placental and umbilical cord morphometry measured at delivery are different between SGA and non-SGA infants. Further studies are warranted to investigate the feasibility and accuracy of ultrasound to measure placental and umbilical cord morphometry during pregnancy.